The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1167/17.12.18
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric integration model of the Stiles-Crawford effect of the first kind and its experimental verification

Abstract: The integrated Stiles-Crawford function is commonly used as apodization model for vision through the natural eye pupil. However, this method does not account for possible effects related to the retinal thickness, the large length-to-diameter aspect ratio of the photoreceptors, or the use of nonMaxwellian illumination. Here, we introduce a geometrical optics model to calculate the fraction of overlap between light at the retina and the photoreceptor outer segments where absorption triggers vision. The model, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 47 publications
(58 reference statements)
0
31
0
Order By: Relevance
“…23 A ''Volumetric integration model of the Stiles-Crawford effect of the first kind and its experimental verification'' was therefore developed. 24 However, in this model too, the outer segments, and not the Müller cells, are responsible for the generation of the SC1 effect.…”
Section: Do Portions Of Müller Cells Act As Optical Fibers?mentioning
confidence: 84%
“…23 A ''Volumetric integration model of the Stiles-Crawford effect of the first kind and its experimental verification'' was therefore developed. 24 However, in this model too, the outer segments, and not the Müller cells, are responsible for the generation of the SC1 effect.…”
Section: Do Portions Of Müller Cells Act As Optical Fibers?mentioning
confidence: 84%
“…In turn, scotopic vision shows a lack of directionality [5,7] despite of the fact that rods are similar in shape to foveal cones. Together, these findings show that the shape of individual photoreceptors does not provide a satisfactory explanation of the SCE-I neither in photopic nor scotopic conditions, but rather the density of visual pigments is a possible cause [16,18]. Also, it has been suggested that dynamical phototropism differences between rods and cones might be involved [19].…”
Section: Introductionmentioning
confidence: 88%
“…The peak location of the sensitivity curve determines the pointing direction of cones [2,8] that often has a nasal bias which is more pronounced for myopic eyes [13]. The transition from Maxwellian (point) to Newtonian (normal) view is nontrivial and underestimates the role of the SCE-I in normal vision by up to an order of magnitude as we have recently shown using a mechanical flickering pupil with diameter in the range of 1.4 to 7.4 mm diameter [16] and followingly confirmed by others using a small flickering aperture on a spatial light modulator [17]. Most SCE-I studies have been performed with foveal vision.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter case allows the system to be uniaxial, and therefore, eliminate unwanted displacements and spectral errors arising between the two paths of the previous system . The authors have recently reported on the use of such a technique for direct analysis of the integrated SCE‐I …”
Section: Introductionmentioning
confidence: 99%